2019
DOI: 10.3389/fimmu.2019.02260
|View full text |Cite
|
Sign up to set email alerts
|

Seeking Flavivirus Cross-Protective Immunity

Abstract: The Flavivirus genus is composed by viral serocomplexes with relevant global epidemiological impact. Many areas of the world present both, vector fauna and geographical conditions compatible with co-circulation, importing, emergence, and epidemics of flaviviruses of different serocomplexes. In this study, we aimed to identify both, immunological determinants and patterns of immune response possibly involved in flavivirus serocomplex cross-protection. We searched B and T cells epitopes which were thoroughly sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 61 publications
3
29
0
Order By: Relevance
“…indicated that, following heterologous DENV infection, memory CD8 + T cells expanded that recognized conserved NS proteins (33). In fact, NS3 and NS5 represent the main targets of the CD8 + T cell response to flaviviruses (34, 35). One study reported more cross-reactive T cell responses to full length NS3 helicase, because of higher sequence homology, than that to the protease region alone (36).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…indicated that, following heterologous DENV infection, memory CD8 + T cells expanded that recognized conserved NS proteins (33). In fact, NS3 and NS5 represent the main targets of the CD8 + T cell response to flaviviruses (34, 35). One study reported more cross-reactive T cell responses to full length NS3 helicase, because of higher sequence homology, than that to the protease region alone (36).…”
Section: Discussionmentioning
confidence: 99%
“…In a mouse model, CD8 + T cells can mediate protection against ZIKV (35). DENV-specific cross-reactive CD8 + T cells can also protect (38), and similar responses are detected in humans, where cross-reactive CD8 + T cells specific for DENV display anti-ZIKV effector potential toward ZIKV, mediating direct cytolysis (39).…”
Section: Discussionmentioning
confidence: 99%
“…Various subsets of T cells are essential for efficient infection clearance and for the development of robust antibody responses against flaviviruses. Flavivirus reactive T cell epitopes have been identified in both viral structural and non-structural proteins and for CD8 and CD4 T cells (14,29). Often, we expect that the T cell epitope must be 100% conserved to induce recall of a memory T cell from a previous infection; however, similar epitopes with only minor substitutions often are able to activate T cells as well although with potentially differing degrees of responses (30,31).…”
Section: Flavivirus Cross-reactive T Cell Responsesmentioning
confidence: 99%
“…Epitopes in the E protein that are recognized by neutralizing antibodies reside in the ectodomain portion consisting of DI, DII, and DIII (Fibriansah and Lok, 2016;Dos Santos Franco et al, 2019;Li et al, 2019). Therefore, it is a surprise that a single amino acid substitution at residue 408 within the EH1 domain, downstream of DIII, dramatically reduced the PS180 neutralizing Viremia of Pekin duckling after inoculation with rPS-F408L and rPS.…”
Section: Discussionmentioning
confidence: 99%